PENENTUAN MODEL ANTRIAN DAN PENGUKURAN KINERJA PELAYANAN PLASA TELKOM PAHLAWAN SEMARANG - Ilham Indra Bakti Al-Irsyad; Sugito Sugito; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Plasa Telkom Pahlawan is a place of ministry-owned PT Telkom provided to serve customers of Telkom. To serve its customers, Plasa Telkom Pahlawan operates several kind of services, they are Customer Service, Cashier, Quick Service, Sales and in November 2014 operated new kind of service, it was Flexi Upgrade. As a provider of facility services, the problem of queues is a problem that is absolutely the case and must be considered. Queue situation occurs because the number of customers at a facility of service exceed the capacity available to perform such services. At Plasa Telkom Pahlawan queuing occurs in five different kinds of services. The best queueing models in Customer Service is (M/G/6):(GD:∞:∞) based on simulation level of aspiration, while the best model of Cashier and Quick Service are (M/M/2):(GD:∞:∞), for Sales is (M/M/1):(GD:∞:∞). Especially for Flexi Upgrade, the best model based on simulation level of aspiration is (G/G/6):(GD:∞:∞). From the analyzed model can be concluded that the queueing system available in Plasa Telkom Pahlawan Service is optimal.Keywords : Queuing system, Plasa Telkom Pahlawan, Customer Service, Cashier, Quick Service, Sales, Flexi Upgrade.